Roles of non-governmental organisations in the national climate change governance: a systematic literature review / Siti Melinda Haris, Firuza Begham Mustafa and Raja Noriza Raja Ariffin - Haris, Siti Melinda; Mustafa, Firuza Begham; Raja Ariffin, Raja Noriza (Universiti Teknologi MARA, 2021)
This review aims to examine the roles of non-governmental organisations (NGOs) in climate change governance. This attempt is to understand the contribution of NGOs to climate change governance at the national level. In order to achieve the objective, a systematic review was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and analysed using thematic analysis. Journal articles were searched using two databases, which are Scopus and Web of Science. NGOs play various specific and functional roles in national climate change governance, such as being advocates and activists, innovators, researchers, information providers, representatives, executors, watchdogs, and trainers. The study contributes to the body of knowledge on the current roles of NGOs in national climate change governance. It further suggests the research areas in climate change governance that could be further investigated.